PKM Penggunaan Teknologi Augmented Reality Pelajaran Biologi Untuk Meningkatkan Pemahaman Siswa SMA - Christina Purnama Yanti; Ginantra, Ni Luh Wiwik Sri Rahayu; Theresia Hendrawati; Dewa Ayu Putri Wulandari (Darma Abdi Karya, 2024)
Biology is a science that studies everything about everyday life, such as living things, health, the environment, and biology can also be used to solve problems that occur in everyday life. One of the things that is discussed in biology is viruses. A virus is a living creature with parasitic properties, which means that the life of this living creature depends on other living creatures by infecting the cells of other living creatures. Studying biology at high school level is considered quite important because it is considered to be an opportunity for students to get to know themselves, the environment and the living creatures around them. Based on interviews conducted with Mr. Tisnawan as one of the biology subject teachers at SMA Negeri 8 Denpasar, the results showed that there are challenges in studying the structure and shape of viruses which can influence students' interest in learning, such as the abstract shape of viruses, lack of variation in learning media, and limited equipment and practical space such as microscopes and others. Therefore, the service team plans to introduce teachers and students to the use of Augmented Reality in learning media where the topic used is the structure and shape of viruses in class X high school material. Assistance to teachers and students in using Augmented Reality applications needs to be provided so that teachers and students can use them well. Apart from that, this assistance is also expected to increase teachers' digital literacy in using technology in learning.